2012
DOI: 10.1152/ajpgi.00488.2011
|View full text |Cite
|
Sign up to set email alerts
|

Saturated fat stimulates obesity and hepatic steatosis and affects gut microbiota composition by an enhanced overflow of dietary fat to the distal intestine

Abstract: de Wit N, Derrien M, Bosch-Vermeulen H, Oosterink E, Keshtkar S, Duval C, de Vogel-van den Bosch J, Kleerebezem M, Müller M, van der Meer R. Saturated fat stimulates obesity and hepatic steatosis and affects gut microbiota composition by an enhanced overflow of dietary fat to the distal intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
235
4
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(269 citation statements)
references
References 35 publications
25
235
4
5
Order By: Relevance
“…A previous isocaloric trial in abdominally obese subjects indicated that the present associations may be causal, since replacing SFAs from butter with PUFAs from sunflower oil reduced liver fat (20,22). Thus, together these trials indicate that SFAs (high in 16:0) per se might promote hepatic steatosis, both during isocaloric and hypercaloric conditions.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…A previous isocaloric trial in abdominally obese subjects indicated that the present associations may be causal, since replacing SFAs from butter with PUFAs from sunflower oil reduced liver fat (20,22). Thus, together these trials indicate that SFAs (high in 16:0) per se might promote hepatic steatosis, both during isocaloric and hypercaloric conditions.…”
Section: Discussionsupporting
confidence: 50%
“…In the current study, a fructose-SFA interaction on liver fat is possible since the muffins contained significant amounts of fructose (33). Early animal data showed that carbohydrate-induced lipogenesis was inhibited by adding linoleic acid, whereas palmitate had no effect (34), and SFAs have enhanced steatosis and increased hepatic lipogenesis compared with PUFAs (20,21). Hepatic activity of the lipogenic enzyme SCD-1 may be elevated in steatosis (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are likely also effects from direct exposure of intestinal microbes to FA. A high fat, high SFA palm oil diet caused increased fecal fat in mice (15). This "overflow, " or decreased absorption and increased intestinal SFA transport, was associated with a decrease in diversity index as well as increased relative amounts of Firmicutes members Bacilli and Clostridia.…”
Section: Controlled Alterations Of Fat Intake In Animalsmentioning
confidence: 97%
“…Below, we provide an overview of the most recent reviews on gut microbiota and metabolic diseases. 31,56,[105][106][107][108][109][110] Obesity Gut microbial composition alterations have been extensively described as either potentially causal or protective toward weight gain 111,112 both in human and mouse studies. An analysis of the metabolic phenotypes of eight genetically distinct inbred mouse strains in response to a HFD revealed several variations in their metabolic-related phenotypes and gut microbiota.…”
Section: Metabolic Diseases and The Microbiomementioning
confidence: 99%